Small machine tools for small workpieces : final report of the DFG Priority Program 1476 - Wulfsberg, Jens Peter; Sanders, Adam (Springer, 2017)
This contributed volume presents the research results of the program "Small machine tools for small work pieces" (SPP 1476), funded by the German Research Society (DFG). The book contains the final report of the priority program, presenting novel approached for size-adapted, reconfigurable micro machine tools. The target audience primarily comprises research experts and practitioners in the field of micro machine tools, but the book may also be beneficial for graduate students.
Keywords: Machine-tools -- Design and construction.; elektronické knihy; electronic books